Parental Support Is Associated with Moderate to Vigorous Physical Activity among Chinese Adolescents through the Availability of Physical Activity Resources in the Home Environment and Autonomous Motivation - Jing Zeng; Nan Qiu; Brianna N. Leitzelar; Jialin Fu; Yechuang Wang; Fang Liang; Kai Ding; Justin B. Moore; Yuliang Zou; Rui Li (MDPI AG, 2022)
This study aimed to use a structural equation model (SEM) to determine the association between parental support and moderate to vigorous physical activity (MVPA) among Chinese adolescents and whether the availability of physical activity (PA) resources in the home environment and autonomous motivation of adolescents mediated the association. Data were collected using questionnaires extracted from the Family Life, Activity, Sun, Health, and Eating (FLASHE) study. A final analytical sample of 3738 adolescents was enrolled. A SEM was performed to evaluate the hypothesized associations. It was found that parental support was not only positively directly but also indirectly associated with MVPA in Chinese boys through the home environment (i.e., availability of PA resources) and the autonomous motivation of adolescents. It is worth noting that the above relationships also exist in Chinese girls, except for the regulatory role of autonomous motivation. These findings suggest that future interventions for increasing adolescents' MVPA should focus on health education for parents to provide more PA resources in the home environment and adequately mobilize children's autonomous motivation.